2017
DOI: 10.1139/cjpp-2016-0319
|View full text |Cite
|
Sign up to set email alerts
|

Primary human monocytes differentiate into M2 macrophages and involve Notch-1 pathway

Abstract: The current study investigates whether inhibiting the Notch-1 signaling pathway in primary human monocytes enhances M2 macrophage differentiation. We generated primary human monocytes cell culture model to understand the effect of Notch-1 signaling pathway. Monocytes were treated with Notch-1inhibitors DAPT or siRNA. Our data show that there was a significant increase in the M1 macrophage population demonstrated by iNOS marker in the primary human monocytes treated with apoptotic conditioned medium (ACM). Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Defects in NF-κB p50 nuclear localization were observed in DAPT-treated macrophages and in RBP-Jκ-deficent macrophages, indicative of crosstalk between Notch and NF-κB pathways [275]. Lastly, DAPT treatment during MI diminished the number of macrophages in the infarcted area and significantly increased the M2 macrophage polarization [276], data resembling those obtained by Singla et al that confirmed reduction of the proinflammatory M1 phenotype following monocyte treatment with DAPT or Notch-1 siRNA [277].…”
Section: Notch In Macrophagessupporting
confidence: 77%
“…Defects in NF-κB p50 nuclear localization were observed in DAPT-treated macrophages and in RBP-Jκ-deficent macrophages, indicative of crosstalk between Notch and NF-κB pathways [275]. Lastly, DAPT treatment during MI diminished the number of macrophages in the infarcted area and significantly increased the M2 macrophage polarization [276], data resembling those obtained by Singla et al that confirmed reduction of the proinflammatory M1 phenotype following monocyte treatment with DAPT or Notch-1 siRNA [277].…”
Section: Notch In Macrophagessupporting
confidence: 77%
“…The regulation and function of Notch signaling in myeloid cells involved in innate immunity is poorly understood. Nevertheless, recent findings elucidate a role for the Notch pathway during TLR-associated and inflammation-induced monocyte differentiation and macrophage activation (Radtke et al, 2010 ; Nakano et al, 2016 ; Singla et al, 2017 ). Cells of the myeloid lineage do express a broad range of TLRs as well as Notch receptors and ligands.…”
Section: Discussionmentioning
confidence: 99%
“…These macrophages exhibited strong antitumor activities in transplanted tumors ( 19 ). Conversely, Notch blockade by GSI, small interfering RNA, or RBP-Jk deletion switches macrophages to M2 phenotype, characterized by the ability to produce IL-10 and an attenuated capacity of activating Th1 cells ( 20 , 21 ). Consistently, T cells activated by RBP-Jk−/− macrophage showed a reduced cytotoxic activity against melanoma cells when compared with wild-type macrophages ( 20 ).…”
Section: Interleukin 10mentioning
confidence: 99%